Who would (not) use all-gender toilets… and why? A study on university students in Taiwan. Issue 2 (1st February 2023) - Peng, Yen-Wen; Wu, Wei-Ning
Abstract: The installation of—and the debates surrounding—all-gender toilets (AGTs) are growing worldwide, but few empirical studies exist regarding the attitudes and behaviors of prospective AGT users. This paper fills the research gap by using a multi-methods approach to investigate how prospective users perceive and use AGTs at National Sun Yat-sen University in Taiwan. Through a survey of 729 university students and a two-week-long on-site observation, the study provides substantive evidence regarding AGTs users. The survey shows that the majority of both male and female respondents endorsed and would actually use AGTs. The presumed opposition to AGTs by mainstream users might have been overestimated. On average, only 9.23% of the respondents disagreed with the installation of AGTs, and only 7.37% never used the AGT next to their classroom. Female students were less likely to endorse and to use AGTs, and were more concerned about privacy, safety and hygiene issues in AGTs. On the other hand, some women would endorse the installation of AGTs even if they don't personally use them. Societies may be able to accommodate these diverse users by allowing for the coexistence of all-gender and gender-segregated toilets. This research contributes to existing gender and toilet literature by providing a cross-examined assessment of prospective respondents' attitudes and behaviors vis-à-vis the AGTs in an actual AGT setting instead of a hypothetical scenario. We encourage future research to target a more diversified pool of respondents to explore the myriad factors associated with mainstream users' attitudes toward and use of AGTs. Supplemental data for this article is available online at https://doi.org/10.1080/0966369X.2021.1987198 .